518 - AUTOIMMUNE DEMENTIA – WHEN TO SUSPECT?. (October 2021) - Caetano, Filipa; Araújo, Margarida; Samouco, Ana; Carvalho, Serafim
Abstract: Background: Autoimune dementias are underrecognized clinical entities, frequently misdiagnosed as neurodegenerative or prion disorders. However, the prognosis is vastly different since immunotherapy can treat these conditions and restore functionality. Research objective: To reflect on autoimmune dementias, briefly presenting the autoimmune syndromes, how to diagnose them and some clinical cues to be attentive of. Methods: Literature search on Pubmed and Google Scholar. Results: The incidence and prevalence of autoimmune dementias are unknown, but autoimmune and inflammatory causes account for 20% of dementia in patients younger than 45 years of age. Autoimmune dementias are classified according to syndromic presentation, specific serologic markers, or histopathologic findings. Patients with autoimmune dementias usually present with an acute or subacute disorder of memory, thinking, or behaviour. Clinical clues that can help clinicians identify autoimmune dementias include six of the following: (i) rapidly progressive or fluctuating course; (ii) multifocal and diverse clinical presentations; (iii) personal or family history of autoimmunity; (iv) detection of inflammatory markers in the cerebrospinal fluid; (v) presence of a neural-specific autoantibody and (vi) favourable response to a trial of immunotherapy. Also, unsuspected cancer, new or recurrent, may manifest neurologically as autoimmune dementia. In evaluating patients with dementia and autoimmune disease, clinicians should be aware of the possible coexistence of these disorders. Conclusions: Recognition of clinical and serologic clues to autoimmune dementia allows early and sustained treatment. Misdiagnosis of a potentially reversible condition as a progressive neurodegenerative disorder can have devastating consequences for the patient and family.